2007
DOI: 10.1016/j.bbabio.2007.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of Photosystem I and Photosystem II in red alga Cyanidium caldarium: Encounter of cyanobacterial and higher plant concepts

Abstract: Structure and organisation of Photosystem I and Photosystem II isolated from red alga Cyanidium caldarium was determined by electron microscopy and single particle image analysis. The overall structure of Photosystem II was found to be similar to that known from cyanobacteria. The location of additional 20 kDa (PsbQ') extrinsic protein that forms part of the oxygen evolving complex was suggested to be in the vicinity of cytochrome c-550 (PsbV) and the 12 kDa (PsbU) protein. Photosystem I was determined as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 45 publications
8
47
3
2
Order By: Relevance
“…The location of PsbQЈ revealed in the present study is consistent with the site suggested from single particle electron microscopic analysis of PSII from another red alga, C. merolae (43), although a previous microscopic analysis suggested a possibly different location of the PsbQЈ in the red alga at a lower resolution (42). Very recently, however, Liu et al (44) reported that cyano-PsbQ was located in the middle of the PSII dimer between two PsbO subunits from two monomers in the lumenal surface of cyanobacterial PSII and interacts with CP47 instead of CP43, based on the cross-linking of a PsbQ dimer and subsequent mass spectrometric analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The location of PsbQЈ revealed in the present study is consistent with the site suggested from single particle electron microscopic analysis of PSII from another red alga, C. merolae (43), although a previous microscopic analysis suggested a possibly different location of the PsbQЈ in the red alga at a lower resolution (42). Very recently, however, Liu et al (44) reported that cyano-PsbQ was located in the middle of the PSII dimer between two PsbO subunits from two monomers in the lumenal surface of cyanobacterial PSII and interacts with CP47 instead of CP43, based on the cross-linking of a PsbQ dimer and subsequent mass spectrometric analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Red alga is the most primitive eukaryotic algae with their photosynthetic systems resemble in part the prokaryotic cyanobacteria and in part the eukaryotic algae, because the PSII of red algae is associated by phycobilisomes as light-harvesting antenna pigments, whereas its photosystem I binds light-harvesting complex I similar to those found in green algae and higher plant photosystem I (42). So far the structure of PSII has been solved from cyanobacteria at an atomic resolution (5, 6), whereas no crystal structure of eukaryotic PSII has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As an evolutionary intermediate between the photosynthetic apparatus of prokaryotic cyanobacteria and that of the eukaryotes in the green lineage, it contains a mixture of prokaryotic and eukaryotic structural traits. Whereas red algal photosystem I (PSI) resembles a higher plant complex, with an crescent-shaped Chla-binding light-harvesting antenna system asymmetrically bound on one side of the core complex (22)(23), PSII of red algae is structurally similar to the cyanobacterial counterpart in that it contains light-harvesting antenna composed of phycobilisomes, large peripheral membrane complexes formed by phycobiliproteins, instead of Chla/ b-binding antenna proteins that constitute the light-harvesting system of green algae and higher plants.…”
Section: Photosystem II (Psii)mentioning
confidence: 99%
“…Although there have been reports of trimeric forms of PSI in plants (Heinemeyer et al, 2004;Kouril et al, 2005), it is now widely accepted that plant PSI forms only monomeric complexes (Kitmitto et al, 1998;Kouril et al, 2005). Furthermore, it is known that PSI is a monomer in green and red algae (Gardian et al, 2007) as well as in diatoms (Veith and Büchel, 2007).…”
Section: Introductionmentioning
confidence: 99%